Analysis of Neutrophil-Lymphocyte Ratio and Platelet-Lymphocyte Ratio in Dengue-Infected Patients - Sari, Nurul Adha; Julyani, Sri; Harahap, Muhammad Wirawan; Bima, Irmayanti Haidir; Karim, Abdul Mubdi Ardiansar Arifuddin (Jurnal Ilmiah Kesehatan (JIKA), 2025)
Dengue infection, caused by the dengue virus and transmitted by Aedes mosquitoes, remains a significant public health issue in Indonesia. The ability to identify reliable biomarkers for assessing disease severity is critical for improving clinical management. This study aimed to evaluate the relationship between the Neutrophil-to-Lymphocyte Ratio (NLR) and Platelet-to-Lymphocyte Ratio (PLR) as potential biomarkers of severity in dengue infection. An observational cross-sectional design was employed, analyzing 76 dengue cases at RSAU dr. Dody Sardjoto. Data were collected from medical records of patients during the critical fever period (days 4-7). The majority of patients were male and adult, with a higher incidence of Dengue Hemorrhagic Fever (DHF). Statistical analysis showed no significant correlation between NLR and PLR with disease severity (p-value >0,05), although a positive correlation between NLR and PLR was observed. However, neither NLR nor PLR effectively predicted hospitalization duration. These results suggest that while NLR and PLR reflect immune responses in dengue infection, they are not suitable biomarkers for assessing disease severity. Further research is needed to identify more reliable biomarkers for better management of dengue infection.